(untitled) (Journal of the College of Basic Education, 2023)
The effectiveness of the extract of the leaves of the Senna alata plant against dermatophytes was studied in laboratory. Body and include Tinea capitis, Tinea cruris, body and Tinea pedis.The results of this study showed that the extract of senna leaves had a strong antifungal effect against Microsporum canis, Trichophyton rubrum, T. mentagrophytes and Epidermophyton fluccosum. The alcoholic extract using ethanol showed the highest degree of inhibition in T. rubrum and E. fluccosum with inhibition zone of 20.50 and 20.00 mm, respectively. The minimum inhibitory concentration (MIC) was calculated, and the results showed that the minimum inhibitory concentration of senna leaf extract for all studied dermatophytes was 5.0 mg/ml.